2022
DOI: 10.1096/fj.202200544rr
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term simulated microgravity on liver metabolism in rhesus macaques

Abstract: The liver is an essential multifunctional organ and constantly communicates with nearly all the tissues in the body. Spaceflight or simulated microgravity has a significant impact on the livers of rodent models, including lipid accumulation and inflammatory cell infiltration. Whether similar liver lipotoxicity could occur in humans is not known, even though altered circulating cholesterol profile has been reported in astronauts. Using a 42‐day head‐down bed rest (HDBR) model in rhesus macaques, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…A previous study on the effect of long‐term SMG on lipid metabolism in rhesus macaque livers 19 led us to investigate whether SMG exposure would target fat accretion in hepatocytes. Using Oil Red O and Nile red to stain neutral lipids, we found that compared to NG, cells treated with SMG for six days showed more Oil Red O puncta, suggesting more LDs (Figures 2A and S2A).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study on the effect of long‐term SMG on lipid metabolism in rhesus macaque livers 19 led us to investigate whether SMG exposure would target fat accretion in hepatocytes. Using Oil Red O and Nile red to stain neutral lipids, we found that compared to NG, cells treated with SMG for six days showed more Oil Red O puncta, suggesting more LDs (Figures 2A and S2A).…”
Section: Resultsmentioning
confidence: 99%
“…5,9,23 Hindlimb unloading is widely utilized to study the effects of microgravity in mice or rats, and head-down tilt bed rest model for non-human primate-rhesus monkeys or human volunteers is also a classical ground-based model of microgravity. [24][25][26][27][28][29][30] Previous studies have found forebody artery remodeling during microgravity. Simulated microgravity experienced by hindlimb unloading rats induced such thoracic aortic structural and functional changes as increased thoracic aortic stiffness is due to both increased aortic collagen content and enzyme cross-linking activity.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism underlying this phenomenon remains unclear, but vascular remodeling, such as common carotid artery and aortic stiffness, may be an important contributor to postflight cardiovascular deconditioning 5,9,23 . Hindlimb unloading is widely utilized to study the effects of microgravity in mice or rats, and head‐down tilt bed rest model for non‐human primate‐rhesus monkeys or human volunteers is also a classical ground‐based model of microgravity 24–30 . Previous studies have found forebody artery remodeling during microgravity.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, research methods for ground simulation of weightlessness mainly include the head-down-tilt bed rest for humans and the tail suspension experiment for animals . The effects of the spaceflight environment on the cardiovascular, musculoskeletal, immunological, neurological, renal, metabolic, reproductive, and visual systems have been confirmed by simulated microgravity (Wise et al, 2005;Hu et al, 2017;Horie et al, 2018;Li et al, 2022;Zong et al, 2022). Animal earth-based analogs are widely used to investigate disorders that might occur during space missions.…”
Section: Introductionmentioning
confidence: 99%